Hard alloy material for drill bit and preparation method of hard alloy material
By using tungsten carbide powder and cobalt powder of different particle sizes, combined with metallographic regulators of nickel-coated carbon nanotubes, oil field drill bit carbide with high toughness and wear resistance, solving the problem of existing drill bit alloy teeth in drilling wells The problems of wear resistance, tooth breakage and corrosion that are prone to occur during the process extend the service life of the drill bit.
Patent Information
- Application Number
- CN202411566375.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The existing oilfield drill bit alloy teeth are prone to abnormal conditions such as wear resistance, crushing teeth, corrosion during the drilling process, resulting in the stopping of drilling construction, prolonging of construction period, and even the drilling is scrapped.
Two different particle size tungsten carbide powder and cobalt powder are used to prepare cemented carbide through sintering process, and a special metallographic regulator is added. The regulator is made of nickel-coated carbon nanotubes, which is evenly dispersed through ball milling process to enhance Toughness and wear resistance of alloys.
It significantly improves the toughness and wear resistance of the alloy material, extends the service life of the drill bit, and improves the efficiency and reliability of drilling construction.
Smart Images

Figure BDA0005119353590000081 
Figure BDA0005119353590000091
Abstract
Description
Technical Field
[0001] The present application relates to an oilfield drill bit, and in particular to a cemented carbide material for the drill bit and a preparation method thereof. Background Art
[0002] The drilling depth of oil fields is generally thousands of meters or even tens of thousands of meters, and the construction period is long. If the alloy teeth are not wear-resistant, broken, corroded, and other abnormal conditions occur during the drilling process, the drilling construction will be stopped, the construction period will be extended, and even the drilling will be scrapped. The alloy teeth used in the three-cone drill bit must have excellent wear resistance, toughness, and corrosion resistance to ensure that it can drill smoothly to the designed depth of the oil well.
[0003] The alloy teeth used in the current three-cone drill bits (hereinafter referred to as oilfield teeth) are usually tungsten-cobalt alloys, the main components of which are tungsten carbide and cobalt. The cobalt content is about 10% to 17%, and the tungsten carbide particle size is about 2.4 to 3.6μm, which is a coarse-grained alloy. The wear resistance and toughness of tungsten-cobalt alloys are a pair of contradictions. The wear resistance is provided by tungsten carbide, while the toughness is provided by cobalt. Generally speaking, the finer the tungsten carbide grains and the less the cobalt content, the higher the hardness, the better the wear resistance, and the worse the toughness; vice versa.
[0004] Traditional ordinary coarse-grained oilfield teeth generally have a hardness of 85.0 to 87.5, wear quickly, have a generally short life during use, and have low drilling depths. To overcome this problem, the number of drill teeth and the diameter of the teeth are usually increased to reduce the wear rate of a single tooth and increase the service life of the drill bit, but this increases material costs. Summary of the invention
[0005] In order to increase the service life of a drill bit, a cemented carbide for a drill bit and a preparation method thereof are provided.
[0006] The above first invention objective of the present invention is achieved through the following technical solutions: A cemented carbide for a drill bit is obtained by sintering raw material powder, wherein the raw material powder comprises the following components in parts by mass: First, 30 to 50 parts of tungsten carbide grains, 40 to 60 parts of the second tungsten carbide grains, 10-17 parts of cobalt powder, The first tungsten carbide grain size is 2-3 μm, the second tungsten carbide grain size is 9-12 μm, The particle size of the cobalt powder is 0.6 to 1.5 μm; 1 to 2.1 parts of a metallographic regulator, the particle size of the metallographic regulator is 9 to 12 μm, and the metallographic regulator is obtained by coating carbon nanotubes with nickel.
[0007] The preparation method of the metallographic conditioning agent is as follows: The carbon nanotubes and the dispersion medium are mixed into a mixed solution, the mixed solution is stirred evenly and then sprayed on a nickel foil, and after drying, another layer of nickel foil is covered, and a composite film is obtained by rolling; The composite film is cut into pieces and ball-milled to obtain a metallographic regulator of the desired particle size.
[0008] By adopting the above technical solution, two kinds of tungsten carbide powders with different particle sizes are used as raw materials, so that the coarse grains and fine grains of tungsten carbide in the alloy structure are reasonably matched. The fine grains have high hardness to provide wear resistance, and the coarse grains can resist crack propagation and thus provide toughness. In addition, the carbon nanotubes are first dispersed in the mixed liquid, then transferred between two layers of nickel foil, and then ball-milled. The carbon nanotubes are located between the two layers of nickel foil, which reduces the possibility of collision, deformation, or even breakage of the carbon nanotubes and the high-speed rotating abrasive during the ball milling process. At the same time, the grinding of the abrasive forms a strong bond between the carbon nanotubes and the nickel, and then the carbon nanotubes are relatively complete and evenly dispersed in the metallographic regulator after ball milling; the metallographic regulator is mixed with other raw materials for sintering, and the metal of the metallographic regulator forms a eutectic with cobalt and forms an alloy with tungsten carbide, bringing the carbon nanotubes into the alloy material more completely, and through the performance enhancement brought by the carbon nanotubes and the change of the metallographic structure of the alloy sintering interface, the strength of the interface between the coarse-grained and fine-grained tungsten carbides is high and the toughness at the interface is good, thereby amplifying the combination effect of the coarse-grained and fine-grained tungsten carbides, and finally significantly improving the toughness and wear resistance of the alloy material, and obtaining a material with good comprehensive performance.
[0009] Optionally, the dispersion medium is a mixture of ethanol and polyethylene glycol 400.
[0010] By adopting the above technical solution, ethanol is a good dispersion system for carbon nanotubes, and polyethylene glycol 400 acts as a surfactant to promote the dispersion of carbon nanotubes, so that the carbon nanotubes are more evenly distributed on the nickel foil, and the resulting metallographic regulator has a better effect; in addition, polyethylene glycol 400 can adjust the viscosity of the mixed liquid, making it easier for the mixed liquid to adhere to the nickel foil and facilitate production.
[0011] Optionally: the dispersion medium is isopropanol and polyethylene glycol in a mass ratio of 100:(1.8-2.6).
[0012] By adopting the above technical solution, the obtained alloy has good toughness and wear resistance.
[0013] Optionally, the cobalt powder is spherical cobalt powder with a purity greater than 99.4wt%.
[0014] By adopting the above technical solution, the cobalt powder is a high-purity spherical cobalt powder with a particle size of 0.6 to 1.5 μm. As a bonding phase, the metallographic structure of the bonding interface after sintering with tungsten carbide is denser, the toughness is better, and the overall performance of the alloy is better.
[0015] Optionally: the first tungsten carbide grains and the second tungsten carbide grains are both subjected to high-temperature carburization treatment, and the high-temperature carburization treatment temperature is not less than 1750° C., which is lower than the melting point of tungsten carbide.
[0016] By adopting the above technical scheme, after high-temperature carburization treatment at 1750-2100°C, the tungsten carbide has complete crystallization and grain boundaries, high hardness and good toughness compared to ordinary tungsten carbide, and is not easy to be ground during the ball milling process; and at the sintering temperature of the alloy material of 1430-1500°C, the tungsten carbide grains are not easy to grow abnormally, making the overall performance of the alloy better and more stable.
[0017] Optionally, the composition further comprises 0.1 to 0.5 parts of a bonding strengthening phase, wherein the bonding strengthening phase is a soluble rare earth salt.
[0018] By adopting the above technical solution and adding trace amounts of rare metal elements, rare earth elements, etc., the comprehensive performance of the material can be improved.
[0019] Optional: The bonding strengthening phase is a compound of ytterbium salt and yttrium salt.
[0020] By adopting the above technical solution, the obtained alloy material has better comprehensive performance.
[0021] The above second invention objective of the present invention is achieved through the following technical solutions: A method for preparing a cemented carbide for a drill bit comprises the following steps: Weigh the raw materials according to the dosage ratio, take the first tungsten carbide grains as raw material group A, take the second tungsten carbide grains as raw material group B, and mix the remaining raw materials as raw material group C. Add raw material group A, part of raw material group C, and grinding media into a ball mill and grind to obtain slurry A. Add raw material group B, the remaining raw material group C, and grinding media into a ball mill and grind to obtain slurry B. After slurry A and slurry B are mixed evenly, slurry C is obtained. The slurry C is spray dried to obtain a mixed material. The mixed material is pressed into shape and sintered to obtain a sintered green tooth.
[0022] By adopting the above technical scheme, the ball milling process of tungsten carbide of different particle sizes is not the same. The ball milling time of coarse-grained tungsten carbide is short, while the ball milling time of fine-grained tungsten carbide is long. By using different ball-to-material ratios and ball milling medium additions, the two types of tungsten carbides are separately ball milled, and the tungsten carbide can reach the best ball milling state, and the resulting alloy material has better toughness and wear resistance.
[0023] In summary, this application has at least the following beneficial effects: 1. The coarse-grained and fine-grained tungsten carbides are reasonably matched in the alloy structure, and a metallographic regulator obtained by a specific preparation method is added. A large number of carbon nanotubes with complete structure are evenly dispersed in the alloy. The performance enhancement brought by the carbon nanotubes and the change of the metallographic structure of the alloy sintering interface ultimately improve the toughness and wear resistance of the alloy material; 2. Carbide is treated at a high temperature of 1750-2100℃. The crystallization and grain boundary of tungsten carbide are complete. Compared with ordinary tungsten carbide, it has high hardness and good toughness. It is not easy to be ground during the ball milling process. And at the sintering temperature of the alloy material of 1430-1500℃, the tungsten carbide grains are not easy to grow abnormally, making the comprehensive performance of the alloy better and more stable. 3. Separately milling the two types of tungsten carbides can achieve the best ball milling state, and the resulting alloy material has better toughness and wear resistance. DETAILED DESCRIPTION
[0024] raw material Tungsten carbide grains: purity is 99.9wt%, specifically there are two particle size specifications, 2-3μm and 9-12μm, which are obtained by secondary screening after being purchased from commercial products.
[0025] Cobalt powder: There are two specific specifications of raw materials; spherical cobalt powder, with a purity of 99.9wt% and a particle size of 0.6-1.5μm, is obtained by secondary screening after purchasing commercial products; polyhedral cobalt powder, with a purity of 99.9wt% and a particle size of 0.6-1.5μm, is obtained by secondary screening after purchasing commercial products.
[0026] Adhesion strengthening phase: a soluble rare earth salt, specifically ytterbium (III) acetate tetrahydrate and yttrium acetate tetrahydrate.
[0027] Nickel foil: pure nickel foil, purity is 99.96wt%, thickness is 0.02mm, weight is 178g / m 2 , customized by Shanghai Lamenette Metal Materials Technology Co., Ltd.
[0028] Nickel powder: purity is 99.96wt%, particle size is 9-12μm, customized by Shanghai Lamenite Metal Materials Technology Co., Ltd.
[0029] Carbon nanotubes: Single-walled carbon nanotubes, with a tube diameter of 10-15nm, a tube length of 5-8μm, a purity of ≥98wt%, an ash content of ≤2%, and a specific surface area of 150-250, customized by Shandong Tanfeng New Materials Technology Co., Ltd.
[0030] Polyethylene glycol 400, ethanol, and polyethylene glycol 800 are commercially available analytical grade products.
[0031] Preparation Example 1 A metallographic regulator, the main components of which are nickel and carbon nanotubes.
[0032] The specific preparation method is as follows: The carbon nanotubes and the dispersion medium are uniformly mixed at a mass ratio of 27.8:100 to obtain a mixed solution, wherein the dispersion medium is a mixture of ethanol and polyethylene glycol 400 at a mass ratio of 100:1.8; A nickel foil is unfolded to obtain a first nickel foil, and the mixed liquid is sprayed on the first nickel foil. After drying, the mixed liquid is sprayed again. After multiple sprayings, the spraying amount of carbon nanotubes reaches 32g / m 2 ; Take another nickel foil and unfold it as the second nickel foil, align the second nickel foil and cover it on the carbon nanotube spraying surface, then use a roller to laminate the first nickel foil and the second nickel foil under a roller pressure of 0.04 MPa, trim and remove the unaligned edge parts, and obtain a composite film; The composite film was cut into pieces of 1 cm×1 cm, and the pieces were put into a ball mill for step-by-step ball milling to obtain a metallographic regulator with a particle size of 9 to 12 μm.
[0033] After testing, the nickel content is 90.92wt%, the carbon nanotube content is 9.05wt%, and the rest are inevitable impurities.
[0034] Preparation Example 2 A metallographic regulator, which differs from Preparation Example 1 in that the mixing medium of the mixed liquid is dichloromethane.
[0035] Preparation Example 3 A metallographic regulator, which differs from Preparation Example 1 in that the mixed medium of the mixed liquid is obtained by mixing ethanol and polyethylene glycol 400 in a mass ratio of 100:0.8.
[0036] Preparation Example 4 A metallographic regulator, which differs from Preparation Example 1 in that the mixed medium of the mixed liquid is obtained by mixing ethanol and polyethylene glycol 400 in a mass ratio of 100:1.3.
[0037] Preparation Example 5 A metallographic regulator, which differs from Preparation Example 1 in that the mixed medium of the mixed liquid is obtained by mixing ethanol and polyethylene glycol 400 in a mass ratio of 100:2.1.
[0038] Preparation Example 6 A metallographic regulator, which differs from Preparation Example 1 in that the mixed medium of the mixed liquid is obtained by mixing ethanol and polyethylene glycol 400 in a mass ratio of 100:2.6.
[0039] Preparation Example 7 A modified tungsten carbide grain is obtained by high-temperature carbonization treatment using tungsten carbide grains of 2 to 3 μm as raw materials.
[0040] The 2-3 μm tungsten carbide grains and polyethylene glycol 400 were uniformly mixed in a mass ratio of 100:1.2, and the polyethylene glycol 400 was carbonized at 1750°C in an argon atmosphere for 7 hours. After the treatment, the temperature was lowered to 1500°C and kept for 3 hours, and then naturally cooled under the protection of argon to obtain modified tungsten carbide grains.
[0041] Preparation Example 8 A modified tungsten carbide grain is different from Preparation Example 7 in that the modified tungsten carbide grain is prepared by uniformly mixing 9-12 μm tungsten carbide grains and polyethylene glycol 400 at a mass ratio of 100:6.4.
[0042] Example 1 A hard alloy for a drill bit, the raw materials of which include first tungsten carbide grains, second tungsten carbide grains, cobalt powder, a metallographic regulator, and a bonding strengthening phase.
[0043] The first tungsten carbide grains are prepared in Preparation Example 7; the second tungsten carbide grains are prepared in Preparation Example 8; the cobalt powder is spherical cobalt powder; the metallographic regulator is prepared in Preparation Example 1; and the bonding strengthening phase is a mixture of ytterbium (III) acetate tetrahydrate and yttrium acetate tetrahydrate in a mass ratio of 4:3.3.
[0044] The specific preparation method is as follows: Take 380g of the first tungsten carbide grains as raw material group A, take 520g of the second tungsten carbide grains as raw material group B, and mix 160g of cobalt powder, 4g of bonding strengthening phase, and 18g of metallographic regulator as raw material group C; Add raw material group A, 85.7g of raw material group C and grinding media into a ball mill for ball milling, with the grinding media added at 0.25L / kg (grinding material), grinding balls φ5mm, 35 rpm, ball-to-material ratio 4:1, and ball milling time of 30h to obtain slurry A. Add raw material group B, 117.3g of raw material group C and grinding media into a ball mill for ball milling, with the grinding media added at 0.15L / kg (grinding material), grinding balls φ5mm, 22 rpm, ball-to-material ratio 2:1, and ball milling time of 30h to obtain slurry B. Slurry A and slurry B are evenly mixed to obtain slurry C. The slurry C was spray dried to obtain a 400 μm mixed material. The mixture is pressed into shape to obtain a tooth blank, and the blank is pressure sintered at a sintering temperature of 1480° C., a pressure sintering pressure of 7.5 MPa, and a sintering time of 95 min to obtain a sintered blank tooth.
[0045] The grinding media consisted of 92 wt % ethanol, 6 wt % water and 2 wt % polyethylene glycol (polyethylene glycol 800).
[0046] If a test sample is prepared, the mixed material is pressed into a sample body, and then sintered to obtain a sample blank.
[0047] Comparative Example 1 A cemented carbide for a drill bit, which differs from Example 1 in that an equal mass of cobalt powder is used to replace a metallographic regulator in a raw material.
[0048] Comparative Example 2 A cemented carbide for a drill bit, which differs from Example 1 in that 18 g of a metallographic regulator in the raw material is replaced by 1.61 g of a carbon fiber tube and 16.39 g of nickel powder.
[0049] Comparative Example 3 A cemented carbide for a drill bit, which is different from the embodiment 1 in that the tungsten carbide grains are single first tungsten carbide grains.
[0050] The differences in preparation methods are as follows: Take 900g of the first tungsten carbide grains as raw material group A, and mix 160g of cobalt powder, 4g of bonding strengthening phase, and 18g of metallographic regulator as raw material group C; Add raw material group A, raw material group C and grinding media into a ball mill for ball milling. The amount of grinding media added is 0.25L / kg (grinding material), the grinding ball is φ5mm, the speed is 35 rpm, the ball-to-material ratio is 4:1, and the ball milling time is 30h to obtain slurry A. The slurry A was spray dried to obtain a 400 μm mixed material. The mixture is pressed into shape to obtain a tooth blank, and the blank is pressure sintered at a sintering temperature of 1480° C., a pressure sintering pressure of 7.5 MPa, and a sintering time of 95 min to obtain a sintered blank tooth.
[0051] The grinding media consisted of 92 wt % ethanol, 6 wt % water and 2 wt % polyethylene glycol (polyethylene glycol 800).
[0052] Comparative Example 4 A cemented carbide for a drill bit, which is different from the embodiment 1 in that the tungsten carbide grains are single second tungsten carbide grains.
[0053] The differences in preparation methods are as follows: Take 900g of the second tungsten carbide grains as raw material group B, and mix 160g of cobalt powder, 4g of bonding strengthening phase, and 18g of metallographic regulator as raw material group C; Add raw material group B, raw material group C and grinding media into a ball mill for ball milling. The amount of grinding media added is 0.15 L / kg (grinding material), the grinding ball is φ5 mm, the speed is 22 rpm, the ball-to-material ratio is 2:1, and the ball milling time is 30 h to obtain slurry B. The slurry B was spray dried to obtain a 400 μm mixed material. The mixture is pressed into shape to obtain a tooth blank, and the blank is pressure sintered at a sintering temperature of 1480° C., a pressure sintering pressure of 7.5 MPa, and a sintering time of 95 min to obtain a sintered blank tooth.
[0054] The grinding media consisted of 92 wt % ethanol, 6 wt % water and 2 wt % polyethylene glycol (polyethylene glycol 800).
[0055] Example 2 A cemented carbide for a drill bit, which is different from Example 1 in that the metallographic regulator is prepared by Preparation Example 2.
[0056] Example 3 A cemented carbide for a drill bit, which is different from Example 1 in that the metallographic regulator is prepared by Preparation Example 3.
[0057] Example 4 A cemented carbide for a drill bit, which is different from Example 1 in that the metallographic regulator is prepared by Preparation Example 4.
[0058] Example 5 A cemented carbide for a drill bit, which is different from Example 1 in that the metallographic regulator is prepared by Preparation Example 5.
[0059] Example 6 A cemented carbide for a drill bit, which is different from Example 1 in that the metallographic regulator is prepared by Preparation Example 6.
[0060] Example 7 A cemented carbide for a drill bit, which is different from Example 1 in that the cobalt powder in the raw material is polyhedral cobalt powder.
[0061] Example 8 A cemented carbide for a drill bit, which differs from Example 1 in that the first tungsten carbide grains are 2-3 μm tungsten carbide grains that have not been subjected to high-temperature carburization treatment, and the second tungsten carbide grains are 9-12 μm tungsten carbide grains that have not been subjected to high-temperature carburization treatment.
[0062] Example 9 A cemented carbide for a drill bit, which differs from Example 1 in that an equal mass of cobalt powder is used to replace the bonding strengthening phase.
[0063] Example 10 A cemented carbide for a drill bit, which differs from Example 1 in that the bonding strengthening phase is ytterbium (III) acetate tetrahydrate.
[0064] Embodiment 11 A cemented carbide for a drill bit, which differs from Example 1 in that the bonding strengthening phase is yttrium acetate tetrahydrate.
[0065] Example 12 A cemented carbide for a drill bit, which is different from Example 1 in that the preparation method is different, as follows: Take 380g of the first tungsten carbide grains as raw material group A, take 520g of the second tungsten carbide grains as raw material group B, and mix 160g of cobalt powder, 4g of bonding strengthening phase, and 18g of metallographic regulator as raw material group C; Add raw material group A, raw material group B, raw material group C and grinding media into a ball mill for ball milling. The amount of grinding media added is 0.25 L / kg (grinding material), the grinding ball is φ5 mm, the speed is 35 rpm, the ball-to-material ratio is 3:1, and the ball milling time is 30 h to obtain slurry C. The slurry C is spray-dried to obtain a 400 μm mixed material. The mixture is pressed into shape to obtain a tooth blank, and the blank is pressure sintered at a sintering temperature of 1480° C., a pressure sintering pressure of 7.5 MPa, and a sintering time of 95 min to obtain a sintered blank tooth.
[0066] The grinding media consisted of 92 wt % ethanol, 6 wt % water and 2 wt % polyethylene glycol (polyethylene glycol 800).
[0067] Embodiment 13 A cemented carbide for a drill bit, which is different from Example 1 in the amount of raw materials used, specifically: Raw material group A is 300 g of first tungsten carbide grains; Raw material group B is 400 g of second tungsten carbide grains; Raw material group C is 100g cobalt powder, 1g bonding strengthening phase, and 10g metallographic regulator; Raw material group A and 53.6 g raw material group C were ball-milled to obtain slurry A; The raw material group B and 71.4 g of the raw material group C were ball-milled to obtain slurry B.
[0068] Embodiment 14 A cemented carbide for a drill bit, which is different from Example 1 in the amount of raw materials used, specifically: Raw material group A is 500 g of first tungsten carbide grains; Raw material group B is 600g of second tungsten carbide grains; Raw material group C is 170g cobalt powder, 5g bonding strengthening phase, and 20g metallographic regulator; Raw material group A and 98.6 g raw material group C were ball-milled to obtain slurry A; The raw material group B and 118.4 g of the raw material group C were ball-milled to obtain slurry B.
[0069] The alloy materials of Examples 1 to 14 and Comparative Examples 1 to 4 were tested for fracture toughness, wear resistance, and bending strength.
[0070] Fracture toughness: Tested according to GB / T 23806-2009, the test results are expressed in fracture toughness MPa / m 2 express.
[0071] Wear resistance: Tested according to GB / T 34501-2017. The test results are expressed as volume wear. The smaller the volume wear, the better the wear resistance.
[0072] Bending strength: Tested according to GB / T 3851-2015, the test results are expressed in bending strength. The test results are shown in the table below.
[0073] Table 1. Test results of Examples 1 to 12 and Comparative Examples 1 to 4 As shown in Table 1, compared with Example 1 and Comparative Examples 1 to 4, the raw materials of Example 1 use the metallographic regulator of Preparation Example 1 and tungsten carbide grains of coarse and fine particle sizes. Compared with Example 1, Comparative Example 1 does not add a metallographic regulator; Compared with Example 1, Comparative Example 2 replaces the metallographic regulator with nickel powder and carbon nanotubes; Compared with Example 1, Comparative Example 3 only uses fine-particle-sized tungsten carbide grains; Compared with Example 1, Comparative Example 4 only uses coarse-particle-sized tungsten carbide grains.
[0074] In the test results, the fracture toughness and bending strength of Example 1 are significantly greater than those of Comparative Examples 1 to 4, and the volume wear of Example 1 is significantly less than that of Comparative Examples 1 to 4. However, the test results of Comparative Examples 1 to 2 are not significantly ahead of those of Comparative Examples 3 to 4, and are weaker than those of Comparative Examples 3 to 4 in some individual properties.
[0075] This is achieved by the use of the metallographic regulator and coarse and fine tungsten carbide grains in combination in Example 1. In Example 1, two tungsten carbide powders of different particle sizes are used as raw materials to reasonably match the coarse grains and fine grains of tungsten carbide in the alloy structure. The high hardness of the fine grains provides wear resistance, and the coarse grains can resist crack propagation and thus provide toughness. At the same time, during the preparation of the metallographic regulator in Example 1, the two layers of nickel foil protect the carbon nanotubes, reduce the possibility of collision, deformation, or even breakage of the carbon nanotubes with the high-speed rotating abrasive during the ball milling process, and use the grinding of the abrasive to form a strong bond between the carbon nanotubes and the nickel, thereby making the carbon nanotubes more complete. The carbon nanotubes are fully and evenly dispersed in the metallographic regulator after ball milling. Then, during the sintering process, the metal in the metallographic regulator forms a eutectic with cobalt and forms an alloy with tungsten carbide, bringing the carbon nanotubes into the alloy material more completely. The performance enhancement brought by the carbon nanotubes and the change of the metallographic structure of the alloy sintering interface make the interface strength between coarse-grained and fine-grained tungsten carbide high and the toughness at the bonding interface good, thereby amplifying the combination effect of coarse-grained and fine-grained tungsten carbide, and finally significantly improving the toughness and wear resistance of the alloy material, and obtaining a material with good comprehensive performance.
[0076] By comparing Example 1 and Example 2, it can be seen that the fracture toughness and bending strength of Example 1 are greater than those of Example 2, and the volume wear loss of Example 1 is less than that of Example 2. This is because the carbon nanotubes are more uniformly dispersed in the mixed liquid and distributed on the nickel foil during the preparation process of the metallographic regulator used in Example 1 than those used in Example 2. Therefore, it is preferred that the dispersion liquid used for the metallographic regulator of the present application is a mixture of ethanol and polyethylene glycol 400.
[0077] In combination with Examples 3 to 6, the fracture toughness and flexural strength of Examples 1 and 5 to 6 are greater than those of Examples 3 to 4, and the volume wear of Examples 1 and 5 to 6 is less than that of Examples 3 to 4; the fracture toughness and flexural strength of Example 5 are greater than those of Example 6, and the volume wear of Example 5 is less than that of Example 6, so the mass ratio of the dispersion nickel ethanol and polyethylene glycol 400 in the present application is 100:(1.8 to 2.6).
[0078] Comparing Example 1 and Example 7, the fracture toughness and bending strength of Example 1 are greater than those of Example 7, and the volume wear of Example 1 is less than that of Example 7. It can be seen that cobalt is used as a bonding phase of the alloy material. In this application, high-purity spherical cobalt powder is selected, and the metallographic structure of the bonding interface after sintering with tungsten carbide is denser, the toughness is better, and the overall performance of the alloy is better.
[0079] Comparing Example 1 and Example 8, the fracture toughness and bending strength of Example 1 are greater than those of Example 8, and the volume wear of Example 1 is less than that of Example 8. This is because the tungsten carbide after high-temperature carburization treatment has complete crystallization and grain boundaries, high hardness and good toughness compared to ordinary tungsten carbide, is not easy to be ground during the ball milling process, and at the sintering temperature of the alloy material of 1430-1500°C, the tungsten carbide grains are not easy to grow abnormally, which makes the overall performance of the alloy better and more stable.
[0080] Adding trace amounts of rare metal elements, rare earth elements, etc. improves the comprehensive performance of the material. By comparing Example 1 with Example 9, it can be verified that the fracture toughness and bending strength of Example 1 are greater than those of Example 9, and the volume wear of Example 1 is less than that of Example 9.
[0081] Combined with Examples 10 to 11, the fracture toughness and bending strength of Example 1 are greater than those of Examples 10 to 11, and the volume wear of Example 1 is less than that of Examples 10 to 11. It can be seen that the bonding strengthening phase in the present application is a compound of ytterbium salt and yttrium salt, and the resulting alloy material has better comprehensive performance.
[0082] In addition, the preparation method of the alloy is also optimized in the present application. The ball milling process of tungsten carbide of different particle sizes in Example 1 is not the same. The ball milling time of coarse-grained tungsten carbide is short, while the ball milling time of fine-grained tungsten carbide is long. Different ball-to-material ratios and ball milling medium addition amounts are used to separately ball mill the two types of tungsten carbides, so that the tungsten carbide can reach the optimal ball milling state. In the test results, the fracture toughness and bending strength of Example 1 are greater than those of Example 12, and the volume wear of Example 1 is less than that of Example 12. The comprehensive performance of the alloy material obtained in Example 1 is better.
[0083] Combining comparative examples 1 to 4 and embodiments 13 to 14, the test results show that the fracture toughness and bending strength of embodiments 13 to 14 are significantly greater than those of comparative examples 1 to 4, and the volume wear of embodiments 13 to 14 is significantly less than that of comparative examples 1 to 4. Therefore, the amount of alloy raw materials used in this application is controlled at 30 to 50 parts by mass of the first tungsten carbide grains, 40 to 60 parts of the second tungsten carbide grains, 10 to 17 parts of cobalt powder, 2.4 to 4.2 parts of metallographic regulator, and 0.1 to 0.5 parts of bonding strengthening phase to obtain a cemented carbide for drill bits with excellent comprehensive performance of fracture toughness and wear resistance, thereby improving the service life of the drill bit.
[0084] This specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but as long as it is within the scope of protection required by the present invention, it will be protected by the patent law.
Claims
1. A cemented carbide for a drill, characterized in that: It is obtained by sintering raw material powder, and the raw material powder includes the following components by mass: First, 30~50 parts of tungsten carbide grains, The second tungsten carbide grains are 40 to 60 parts, 10~17 parts of cobalt powder, The first tungsten carbide grain size is 2-3 μm, the second tungsten carbide grain size is 9-12 μm, The particle size of the cobalt powder is 0.6-1.5 μm; 1-2.1 parts of metallographic regulator, the particle size of the metallographic regulator is 9-12 μm, and the metallographic regulator is obtained by nickel-coated carbon nanotubes, The preparation method of the metallographic conditioning agent is as follows: The carbon nanotubes and the dispersion medium are mixed into a mixed solution, the mixed solution is stirred evenly and then sprayed on a nickel foil, and after drying, another layer of nickel foil is covered, and a composite film is obtained by rolling; The composite film is cut into pieces and ball-milled to obtain a metallographic regulator of the desired particle size.
2. A cemented carbide for a drill according to claim 1, characterized in that: The dispersion medium is a mixture of ethanol and polyethylene glycol 400.
3. A cemented carbide for a drill according to claim 2, characterized in that: The dispersion medium is ethanol and polyethylene glycol in a mass ratio of 100:(1.8-2.6).
4. The cemented carbide for a drill according to claim 1, characterized in that: The cobalt powder is high-purity spherical cobalt powder with a purity greater than 99.4wt%.
5. The cemented carbide for a drill according to claim 1, characterized in that: The first tungsten carbide grains and the second tungsten carbide grains are both subjected to high-temperature carburization treatment, wherein the high-temperature carburization treatment temperature is not less than 1750° C., which is lower than the melting point of tungsten carbide.
6. The cemented carbide for a drill according to claim 1, characterized in that: It also includes 0.1 to 0.5 parts of a bonding strengthening phase, wherein the bonding strengthening phase is a soluble rare earth salt.
7. The cemented carbide for a drill according to claim 1, characterized in that: The bonding strengthening phase is a compound of ytterbium salt and yttrium salt.
8. The method for preparing a cemented carbide for a drill according to any one of claims 1 to 7, characterized in that: The following steps are involved: Weigh the raw materials according to the dosage ratio, take the first tungsten carbide grains as raw material group A, take the second tungsten carbide grains as raw material group B, and mix the remaining raw materials as raw material group C. Add raw material group A, part of raw material group C, and grinding media into a ball mill and grind to obtain slurry A. Add raw material group B, the remaining raw material group C, and grinding media into a ball mill and grind to obtain slurry B. After slurry A and slurry B are mixed evenly, slurry C is obtained. The slurry C is spray dried to obtain a mixed material. The mixed material is pressed into shape and sintered to obtain a sintered green tooth.
Citation Information
Patent Citations
Hard alloy for mining tools and preparation method of hard alloy
CN107447154A
Non-uniform hard alloy prepared by adopting close-packed batching mode and preparation method thereof
CN111455252A
Hard alloy and preparation method and application thereof
CN112342449A
Sintered hard alloy and duplex coated sintered hard alloy composed by forming film on surface of same alloy
JP1990073946A
Cemented carbide and method of manufacturing the same
JP2013040396A
Cited By
High-wear-resistance hard alloy drill bit and preparation method thereof
CN120961923A
High wear-resistant cemented carbide drill bit and preparation method thereof
CN120961923B